The Influence Of Good Corporate Governance On Firm Value With Financial Performance As A Moderation - Arisky Andrinaldo; Indrawati Mara Kesuma; Retno Ulfayatun Hidayah; Randi Alfarizi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the effect of good corporate governance on firm value in food and beverage companies on the Indonesia Stock Exchange with financial performance as a moderating variable. This research is quantitative research. The number of companies in the food and beverages subsector consists of 30 (thirty) companies. The sample in this research consisted of 13 companies over 5 years. Data collection is carried out through financial reports. This research data was analyzed using a moderation test. The findings of this research indicate that 1) There is an influence of financial performance on firm value. 2) There is an influence of Independent Commissioners on firm value. 3) There is an influence of Independent Directors on firm value. 4) There is an influence of Independent Audit on firm value. 5) There is a moderating influence of the Independent Commissioner's financial performance on firm value. 6) There is a moderating influence of independent directors' financial performance on firm value. 7) There is a moderating influence of financial performance on Independent Audit on firm value in Food and Beverage Companies on the Indonesian Stock Exchange.